The Impact on TV Advertisement on Childrens Behaviour in Grade Five Students At Ratmalana, Sri Lanka (Global Journal of Management and Business Research, 2017)
The main objective of the study is to seek the influence on television advertising on children in Sri Lanka. The study used primary data with 50 children the age of ten (grade 5) representing Kandawala Maha Vidyalaya, Ratmalana, Sri Lanka. Ten question questionnaire was used by the study group. Fast food and drink advertisements were the most influenced in children behaviour. The adverts based on toys, presents and stickers with the item are mostly attracted by the children on TV advertisement. Possible policy implications suggested for the family, schools, advertising agencies, media and for the government, have been initiated as the final contribution of the study.
Keywords: Fast food and drink advertisements